Improving Squirrel Cage Induction Motor Efficiency: Technical Review - Ramdan, Razali; Abdalla, Ahmed N.; Ruzlaini, Ghoni; Venkataseshaiah, C. (Academic Journals, 2012)
Studying and improving of Squirrel Cage Induction Motor (SCIM) efficiency is a continuous area of interest not only among the researchers but also the industry, manufacturer and government. However, until today there are still struggles to find the most holistic environment of the SCIM which achieve its efficiency at the most lowest cost and at the same time sustaining the performance of the motor. This paper will focus on the method on improving SCIM efficiency. The first discussion presented the main importance of efficient motors and its drive systems. These are partly conceptual, partly concerning circuit topology and current commutation technique. The second discussion ooptimization of SCIM efficiency using intelligent techniques which are of particular interest. The third discussion describes the energy efficiency of SCIM standards and most effect motor parameters on SCIM efficiency.